HUBUNGAN REMINDER MEDICATION CARD TERHADAP KADAR HEMOGLOBIN IBU HAMIL ANEMIA DI PUSKESMAS BUNGAMAS - Podojoyo; Suryani; Sartono; Yulianto; Mia Lestari Peri Putri (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Anemia in pregnant women is a condition where a mother has a hemoglobin level of <11 g/dL in the first and third trimesters or a hemoglobin level of <10.5 g/dL in the second trimester. The results of Basic Health Research (RISKESDAS 2018) show that the proportion of anemia in pregnant women is 48.9%, an increase of 11% compared to RISKESDAS 2013 data of 37.1%. The aim of this research is to determine the influence of pregnant women's knowledge, blood supplement tablet (TTD) consumption, pregnant women's gestational age and hemoglobin levels of anemic pregnant women before and after being given medication reminder media media in the Bungamas Health Center working area. This type of research is quantitative research using a Quasi Experimental research design and a one group pretest posttest design. The sample in this study was 37 samples of anemic pregnant women. Data analysis was carried out univariate and bivariate The results showed that there was a significant difference (p value <0,001) between the hemoglobin levels of anemic pregnant women before and after being given medication reminder media. Conclusion It is necessary to analyze food intake or consumption that is related to the hemoglobin levels of anemic pregnant women.